USING FLASHCARD OF CARTOON CHARACTERS TO TEACH VOCABULARY TO ELEMENTARY SCHOOL STUDENTS - Reisha Rahma Agus; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2016)
Teaching English for young learners is one of the difficult things, if we remember.  There is more than a hundred thousand word of it.Moreover, something that should be remember is there might be many ways which is given by the teacher to teach vocabulary to Elementary school students in order to make them understand and comprehend each of the vocabulary given. Because of that, to encourage them to be more attractive in studying vocabulary, so that the teachers have to prepare one of an interesting, innovative and and creative. This paper will presents about one media which can get students’ attention in comprehending for those vocabularies., it is Flashcard of Cartoon Characters. Flashcard of Cartoon Characters is one of card media English learning which can help teacher to teach vocabulary for students based on the Cartoon characters in every their favorite movies.